The Combination of Propofol and Ketamine Does Not Enhance Clinical Responses to Electroconvulsive Therapy in Major Depression—The Results From the KEOpS Study - Brunelin, Jerome; Iceta, Sylvain; Plaze, Marion; Gaillard, Raphaël; Simon, Louis; Suaud-Chagny, Marie-Françoise; Galvao, Filipe; Poulet, Emmanuel (Frontiers in Pharmacology, 2020)
Objective: We investigated the clinical effects of the combination of ketamine and propofol as anesthetic agents during electroconvulsive therapy (ECT) in patients with uni- or bipolar major depressive episodes. We hypothesized that ketamine may confer short- and long- term advantages in improving depressive symptoms at the early stages of ECT. Methods: In a randomized placebo-controlled trial, remission rates after 4 and 8 weeks of ECT were compared between patients who were randomly allocated to receive either the combination of ketamine (0.5 mg/kg) + propofol (n= 11) or placebo + propofol (n = 16). Depressive symptoms were assessed weekly using the Montgomery–Åsberg Depression Rating Scale (MADRS); ECT sessions were administered twice per week for a maximum of 8 weeks (16 sessions). Results: After 4 weeks, we observed significantly fewer remitters (MADRS score < 10) in the ketamine + propofol group (0/11; 0%) than in the placebo + propofol group (5/16; 31%; χ2 = 4.22; p = 0.040). No significant difference was observed between the two groups regarding the number of patients who achieved remission weekly throughout the study period (Chi² = 3.588; p = 0.058). The mean duration of seizures was significantly shorter in the ketamine + propofol group than in the placebo + propofol group. Conclusions: The results from the current study corroborated results from previously published studies and did not support the use of the combination of ketamine + propofol as an anesthetic agent for ECT in patients with major depressive episodes in clinical settings.